New Podocnemidid Turtle (Testudines: Pleurodira) from the Middle-Upper Paleocene of South America (2010)
A new pleurodiran turtle, Cerrejonemys wayuunaiki, from the middle to upper Paleocene, Cerrejón Formation of Colombia, is described on the basis of a complete skull, lower jaw, partial carapace and plastron, two cervical vertebrae, a right coracoid, and both pelvic girdles. Cerrejonemys wayuunaiki shares a suite of diagnostic characteristics with Podocnemididae, including a fully developed, medially extensive cavum pterygoidei that is almost completely covered by the prolonged posterolateral flanges of the pterygoid, a posterior elongation of the secondary roofing of the skull composed of the parietal and the quadratojugal covering two-thirds or more of the cavum tympani, a dentary covered laterally by the surangular, and no contact between the exoccipital and quadrate. Cerrejonemys wayuunaiki is unique among podocnemidids in having ridges on the ventral margin of the dentary, dentaries that form an acute angle at the fused symphysis, and a relatively thick (up to 35 mm) carapace and plastron. Results from a cladistic analysis of panpodocnemidids indicate that C. wayuunaiki is the sister taxon of the genus Podocnemis, which ranges from the Miocene to Recent, implying that stem of Podocnemis spp. were inhabiting tropical South America early in the Paleogene.